Effect of Vitamin A supplementation on the Serum levels of some Immunoglobulin in Vitamin A deficient children - S. M. Faruque; Yearul Kabir; S. A. M. Khairul Bashar (Indonesian Pediatric Society, 1984)
Effect of vitamin A deficiency and of subsequent vitamin A supplementation on the serum levels of immunoglobulins, lgG, lgA and lgM were studied in children with severe to moderate vitamin A deficiency. Decreased levels of lgG ( P < 0. 001 ), lgA ( P < 0.01 ) and increased levels of serum lgM ( P < 0.01 ) were found in vitamin A deficient children, compared to normal. On supplementation of 100,000-200,000 iu. Of vitamin A, during a period of 2 weeks, serum lgG, IgA and IgM levels in the vitamin A deficient children increased by 49.4 ± 7.2%, 14.2 ± 7. 7%, and 8.0 ± 2.3% respectively with an increase in the serum vitamin A levels by 4 7. 6 ± 10. 6 per cent. The results have been discussed on the possible interactions of vitamin A deficiency and immunity.